High-temperature oxidation of Zrsingle bond1Nb zirconium alloy with protective Cr/Mo coating; Surface and Coatings Technology; Vol. 439 - Syrtanov M. S. Maksim Sergeevich; Kashkarov E. B. Egor Borisovich; Abdulmenova A. V. Anastasiya Vladimirovna; Sidelev D. V. Dmitry Vladimirovich (2022, 2022)
Title screen